Visual and Anatomical Outcomes of Intravitreal Aflibercept for Treatment-Resistant Neovascular Age-Related Macular Degeneration. (7th May 2014) - Gharbiya, Magda; Iannetti, Ludovico; Parisi, Francesco; De Vico, Umberto; Mungo, Maria Laura; Marenco, Marco
Abstract : A retrospective chart review of patients with persistent subretinal and/or intraretinal fluid, despite previous treatment with intravitreal ranibizumab (0.5 mg), who were switched to aflibercept injections, was performed. Treatment was three monthly aflibercept (2 mg) injections followed by dosing on pro re nata basis. Main outcome measures included changes in best corrected visual acuity (BCVA), 1 mm central subfield (CSF) retinal thickness, the height of the pigment epithelial detachment (PED), and subfoveal choroidal thickness on optical coherence tomography at 6 months. Thirty-one eyes of 30 patients were analyzed. The mean number of injections before aflibercept conversion was 34.4 ± 11.9. After an average of 4.5 aflibercept injections (range 3 to 6) over 6 months, no significant change in BCVA was observed (P > 0.05 ). Compared with baseline, there was a significant reduction of the CSF retinal thickness (449 ± 179 versus 269 ± 145  μ m, P < 0.001 ), maximum PED height (262 ± 134 versus 183 ± 100  μ m, P < 0.001 ), and choroidal thickness (192 ± 67 versus 167 ± 51  μ m, P < 0.01 ). Stable visual acuity and anatomical improvement were obtained for up to 6 months after aflibercept conversion. However, choroidal thinning related to treatment was observed.